2007
DOI: 10.1152/ajplung.00181.2006
|View full text |Cite
|
Sign up to set email alerts
|

Secretory phospholipases A2stimulate mucus secretion, induce airway inflammation, and produce secretory hyperresponsiveness to neutrophil elastase in ferret trachea

Abstract: Secretory phospholipases A(2) (sPLA(2)) are increased in the bronchoalveolar lavage fluid of patients with asthma and acute respiratory distress syndrome. Intratracheal sPLA(2) instillation induces acute lung injury in the rat and guinea pig. We hypothesized that sPLA(2) would stimulate mucus secretion in vitro and that intratracheal sPLA(2) exposure would induce mucus hypersecretion and airway inflammation in the ferret trachea in vivo. In vitro, porcine pancreatic sPLA(2) at a concentration of 0.5 or 5 U/ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Although our studies clearly indicate that cPLA2a plays a key role in mucus production, the implication of other PLA2 in this process cannot be excluded. Indeed, it has been shown that secreted PLA2 stimulate mucus secretion in ferret trachea [40].…”
Section: Discussionmentioning
confidence: 99%
“…Although our studies clearly indicate that cPLA2a plays a key role in mucus production, the implication of other PLA2 in this process cannot be excluded. Indeed, it has been shown that secreted PLA2 stimulate mucus secretion in ferret trachea [40].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] We have reported that sPLA 2 stimulate mucus hypersecretion in the ferret trachea through activation of the lipoxygenase (LO) pathway. 11 Mucus obstruction of airways and goblet cell hyperplasia are characteristic of severe asthma. 12,13 IL-13 is increased in asthma and induces goblet cell hyperplasia with mucus hypersecretion in vivo and in vitro.…”
Section: [ 1 4 7 # 6 C H E S T J U N E 2 0 1 5 ]mentioning
confidence: 99%
“…35 We have shown previously that sPLA 2 dramatically increases mucus secretion from the ferret trachea and we called this "secretory hyperresponsiveness." 11 Mucus accumulation and goblet cell hyperplasia in the airway are closely correlated with morbidity and mortality. 36,37 Th e results of the current study suggest that sPLA 2 from ciliated cells, perhaps acting as airway sensory receptors, can increase mucus secretion and production of inflammatory mediators from IL-13-transformed goblet cells.…”
Section: Secretion In Goblet-enriched Cellsmentioning
confidence: 99%
“…Several studies have detected the presence of sPLA 2 in the lung (5,88). In conditions such as asthma, ARDS, and bronchial pneumonia, elevated amounts of sPLA 2 are found in the bronchial/alveolar lavage fluid (BALF) and lung tissue of patients (5,7,18,50,72,88,108).…”
Section: Spla 2 Smentioning
confidence: 99%
“…In conditions such as asthma, ARDS, and bronchial pneumonia, elevated amounts of sPLA 2 are found in the bronchial/alveolar lavage fluid (BALF) and lung tissue of patients (5,7,18,50,72,88,108). In fact, a positive correlation exists between increased levels of sPLA 2 and a poor clinical outcome (5,88). A major source of sPLA 2 is the alveolar macrophage (5).…”
Section: Spla 2 Smentioning
confidence: 99%